Development of Learning Modules for Senior High School Semester V Based on the Independent Curriculum - Natasya, Umy; Hutagalung , Surya Masniari (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research is about the creation of a learning module for the 5th semester of high school based on the Independent Curriculum with the theme